Comparative efficacy of microwave ablation and radiofrequency ablation for treating metastatic liver cancer: a systematic review and meta-analysis - Li, Zheng; Yan, Tingting; Cai, Xiujun (Frontiers in Oncology, 2024)
ObjectiveThis study aims at evaluating and juxtaposing the efficacy of radiofrequency ablation (RFA) and microwave ablation (MWA) for hepatic metastases treatment.MethodsWe undertook an extensive literature search across the Cochrane Library, Web of Science, Embase, PubMed, CNKI, and databases for studies published up to December 2023, assessing the outcomes of RFA versus MWA in hepatic metastases treatment. Studies were included or excluded based on established criteria. Continuous variables were analyzed with the aid of the weighted mean difference (WMD) and its 95% confidence interval (CI), while the odds ratio (OR) with its 95% CI was utilized for dichotomous variables. Data were processed by use of STATA 17.0 software. Key outcomes assessed included ablation time, post-operative local tumor progression (LTP), disease-free survival (DFS), and post-operative complications (POCs).ResultsSeven studies, comprising 357 patients undergoing MWA and 452 patients undergoing RFA, fulfilled the inclusion criteria. As unveiled by the meta-analysis, RFA and MWA did not significantly differ in ablation time, DFS, and POCs. Nonetheless, MWA resulted in a strikingly reduced rate of post-operative LTP versus RFA.ConclusionMWA offers superior control over post-operative LTP, suggesting better overall efficacy in hepatic metastases treatment compared with RFA.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023385201.